Analisis Struktur Naratif dalam Antologi Puisi “Cica 96 Puisi” Karya Cyntha Hariadi: Analysis of Narrative Structure in the Poetry Anthology "Cica 96 Puisi" by Cyntha Hariadi - Nabila Amalia Suhada; Zahra Naswa Fitri; Cindy Puja Aulia; Melisa Anggraini Nusainu; Elmustian Elmustian (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the narrative structure in Cyntha Hariadi's anthology, "Cica 96 Puisi," focusing on the poet's method of constructing narratives through elements of plot, characters, setting, theme, and message. The approach used was qualitative descriptive, using reading and note-taking techniques on 27 poems with dominant narrative elements. The analysis emphasized the relationship between story and discourse within the poetic texts. The results show that "Cica 96 Puisi" presents a complex and reflective narrative structure. The narratives in her poems form a historical mosaic that records the journey of identity, trauma, and social experiences of ethnic Chinese in Indonesia. The plot is structured chronologically and reflectively, moving between the past and the present. The setting and time depict social realities, while the message emphasizes the importance of accepting identity and historical memory as a form of resistance against discrimination. Overall, Cyntha Hariadi successfully constructs poetry as a narrative medium that represents identity, racism, and social criticism through simple yet meaningful poetic language.